2022
DOI: 10.29333/ejmste/11485
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Augmented Reality in Latin-American Engineering Education: A Scoping Review

Abstract: As part of a recent change, Augmented Reality (AR) has filled engineering classrooms, being employed for various pedagogical purposes around the world. However, little is known about the different features and uses of this technology in Latin America. This Scoping Review asks how are educational AR systems designed, used and evaluated in the region, comparing this to the international literature. To address this question, we charted 36 conference papers and scientific articles, taking care of the quality gaps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…AR is a crossover between the real and virtual worlds. The methods developed in augmented reality are currently divided into two, namely, Marker Based Tracking and Marker less Augmented reality [59,61,57]. The results of implementing the use of AR media in biology practicum learning show that the AR media developed is quite effective in helping students understand the concept of the nervous system [56,60,62].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AR is a crossover between the real and virtual worlds. The methods developed in augmented reality are currently divided into two, namely, Marker Based Tracking and Marker less Augmented reality [59,61,57]. The results of implementing the use of AR media in biology practicum learning show that the AR media developed is quite effective in helping students understand the concept of the nervous system [56,60,62].…”
Section: Discussionmentioning
confidence: 99%
“…The results of implementing the use of AR media in biology practicum learning show that the AR media developed is quite effective in helping students understand the concept of the nervous system [56,60,62]. In the opinion of [59] one of the factors that makes students interested in researching biology using AR is the use of 3D animation to make it easier for students to visually represent the biology practicum. Complex becomes easier to describe visually [50,63,57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the focus has been on engineering education but they should experiment with other pedagogies and forms of assessment [3]. It is also necessary to indicate that augmented reality has become a driving force for future learning, even when teachers and students are not geographically together [4].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the unique challenges and opportunities in this region can help identify strategies to promote diversity and inclusion in the field. For example, a study on the use of augmented reality in Latin-American engineering education found that engineering educators in Latin America are leading innovation in design, pedagogy, and research practices (García et al, 2022). This highlights the potential for incorporating innovative teaching methods that promote diversity and inclusion in civil engineering education.…”
Section: Introductionmentioning
confidence: 99%